Model Alternatif Ujian Akhir - Rogers Pakpahan (Badan Standar, Kurikulum, dan Asesmen Pendidikan, Kemendikbudristek, 2012)
This paper is intended as a contribution of idea to the implementation of final examination at the education unit level. Various problems arising in the implementation of the national final examination require improvement efforts through the establishment of an independent assessment agency and anexamination material preparation model. Preparation of test materials is done in two models. The first model is the map of questions is prepared by the school/regional office of education and the question is prepared by the assessment body or the map is prepared by the assessment body while the question is prepared by the school/independent body. The second model, the questions are prepared by the assessment body or the questions are prepared by the school. At each model, the assessment body plays its role toset the score for all examinees so that the scale can be applied nationally. It is therefore the assessment body equalizes the score or grade given by the school so that the score can be used for certification, quality mapping, and enrollment. Determination of score standard is done through a series ofconsiderations with reference to the ability of the examinee. The score standard may be changed pursuant to the student’s competence achievement at every year. ABSTRAK Tulisan ini dimaksudkan sebagai sumbangan pemikiran dalam penyelenggaraan ujian akhir di tingkat satuan pendidikan. Berbagai permasalahan muncul dalam pelaksanaan ujian akhir nasional sehingga diperlukan upaya perbaikan melalui pembentukan lembaga penilaian mandiri dan model penyiapan bahan ujian. Penyusunan bahan ujian dilakukan dalam dua model. Model pertama merupakan penyusunan kisi-kisi oleh sekolah/daerah dan soal disusun oleh lembaga penilaian atau sebaliknya kisi-kisi disusun lembaga penilaian dan soal disusun oleh sekolah atau lembaga independen. Model kedua, soal disediakan oleh lembaga penilaian atau soal disiapkan oleh sekolah. Pada setiap model lembaga penilaian berperan untuk penetapan skor dari seluruh peserta ujian sehingga skala berlaku nasional. Untuk itu, lembaga penilaian menyetarakan skor atau nilai yang dikeluarkan sekolah, sehingga nilai tersebut dapat digunakan untuk sertifikasi, pemetaan mutu, dan untuk seleksi penerimaan siswa baru. Penentuan standar skor dilakukan melalui serangkaian pertimbangan dengan mengacu pada kemampuan peserta ujian. Standar skor setiap tahun dapat diubah sesuai dengan perkembangan pencapaian kompetensi siswa setiap tahun.